2014
DOI: 10.1371/journal.pgen.1004164
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of a Multimodular Bacterial Chemosensory Apparatus

Abstract: Chemosensory systems (CSS) are complex regulatory pathways capable of perceiving external signals and translating them into different cellular behaviors such as motility and development. In the δ-proteobacterium Myxococcus xanthus, chemosensing allows groups of cells to orient themselves and aggregate into specialized multicellular biofilms termed fruiting bodies. M. xanthus contains eight predicted CSS and 21 chemoreceptors. In this work, we systematically deleted genes encoding components of each CSS and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 71 publications
(100 reference statements)
2
37
1
Order By: Relevance
“…Mutations in the Frz pathway alter the frequency of reversals. Fluorescence microscopy revealed that FrzCD localizes in helical filaments that cover the cell length and that FrzCD is dynamic within these structures, continuously changing its position, number, and intensity (74,75). FrzCD in one cell transiently aligns with that in another as cells make side- to-side contacts.…”
Section: Cytoplasmic Chemoreceptors With Dynamic Cytoplasmic Localizamentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the Frz pathway alter the frequency of reversals. Fluorescence microscopy revealed that FrzCD localizes in helical filaments that cover the cell length and that FrzCD is dynamic within these structures, continuously changing its position, number, and intensity (74,75). FrzCD in one cell transiently aligns with that in another as cells make side- to-side contacts.…”
Section: Cytoplasmic Chemoreceptors With Dynamic Cytoplasmic Localizamentioning
confidence: 99%
“…FrzCD appears to respond to the presence of attractants and repellents through levels of methylation, and the modification appears to have consequences on fruiting body formation (8). The second M. xanthus cytoplasmic chemoreceptor, Mcp7, displays subpolar localization at either one or both poles and was the most mobile of the M. xanthus chemoreceptors (75). This chemoreceptor is encoded in the che7 locus with cognate copies of CheA, CheW, CheY, CheB, CheR, and the accessory protein Cpc7.…”
Section: Cytoplasmic Chemoreceptors With Dynamic Cytoplasmic Localizamentioning
confidence: 99%
“…As a control, we looked at the cellular localization of another chemoreceptor fusion, DifA-GFP, in the absence of parB . DifA has been recently shown to form membrane bound and uniformly distributed clusters [28]. In the absence of parB , even cells without nucleoid still carried DifA-GFP clusters and these clusters localized similar to the wild type [28] (Figure 1E).…”
Section: Resultsmentioning
confidence: 85%
“…Fluorescence microscopy has shown that a FrzCD-GFP fusion appears as multiple distributed clusters co-localizing with the nucleoid in M. xanthus cells (Figure 1A, 1B and Figure S1) [2729]. It has been also shown that an inducible FrzE-YFP fusion colocalizes with FrzCD at the nucleoid [29].…”
Section: Resultsmentioning
confidence: 99%
“…The central processing component for all chemosensory systems is CheA. In previous work, we analyzed the M. xanthus genome for cheA homologs and identified four additional clusters, including Che5 to -8 (31,32). Because each cluster contains unique genes predicted to encode novel protein functionality regarding inputs and/or outputs, we further characterized the Che7 system (genes MXAN_6965 to MXAN_ 6957) for its role in development in M. xanthus.…”
Section: Resultsmentioning
confidence: 99%